Radiotherapy for ductal carcinoma of the prostate: an analysis based on the Japanese radiation oncology study group survey. (6th December 2022) - Kawamura, Hidemasa; Nakamura, Katsumasa; Yoshioka, Yasuo; Itasaka, Satoshi; Tomita, Natsuo; Onishi, Masahiro; Iwata, Hiromitsu; Aizawa, Takuya; Kikuchi, Koyo; Nagata, Kenji; Nakamura, Kiyonao; Nishioka, Kentaro; et al.
Abstract: Background: The clinical characteristics of prostate ductal carcinoma is still unclear, and treatment strategy has not yet been established due to its rarity. Therefore, we conducted a multicenter survey of radiation therapy for prostate ductal carcinoma in Japan. Method: Data of patients with ductal carcinoma of the prostate treated with radiation therapy between 1996 and 2018 were extracted from the database of each facility. Results: Fifty-two treatment records of 41 patients were collected from nine institutions. The treatment purpose and situations were varied curative intent to palliation. Twenty-eight patients received curative treatments. The median follow-up period of these patients was 68 months. Androgen deprivation therapy was combined with radiation therapy in 26 cases (93%). X-ray and particle irradiation was used. Radiation dose range was 63–78 Gy; 5-year overall survival, progression-free survival and biochemical relapse-free survival were 87.0, 79.3 and 79.3%, respectively. One patient experienced Grade 3 radiation proctitis and one experienced Grade 3 radiation cystitis. There were no Grade 4 or worse adverse events. Conclusion: Most patient received similar treatment with adenocarcinoma of prostate, and the clinical results were compatible. For more reliable evidence, further studies are required. Abstract : This is the first study to report the results of a nationwide survey in Japan analyzing ductal carcinoma of the prostate treated with radiotherapy.